4D printing of continuous fiber-reinforced electroactive smart composites by coaxial additive manufacturing. (15th July 2023) - Fallah, Ali; Asif, Suleman; Gokcer, Gizem; Koc, Bahattin
Abstract: In this study, a coaxial additive manufacturing process was developed for four-dimensional (4D) printing with continuous carbon fiber-reinforced shape memory polymers (SMPs). These materials have potential applications in the aerospace, automotive, and biomedical industries due to their high strength-to-weight ratio and shape memory properties. The mechanical and thermal properties of the SMPs were evaluated and the effects of printing parameters on printability and carbon fiber volume fraction were analyzed to determine optimal printing conditions. It was found that even a small amount of carbon fiber significantly improved the mechanical properties of the 4D printed samples. The shape memory properties of the printed samples were also examined, and it was found that the structure was able to recover the original shape quickly at low-temperature programming, making it suitable for load-bearing structures. At high-temperature programming, the structure retained the programmed shape well, but recovery of the original shape was slower and incomplete. The use of continuous carbon fiber reinforced SMPs also allows for Joule heating to be used for shape recovery, with the applied voltage able to control the shape recovery process. A high level of deformation recovery (95%) was also achieved in highly deformed structures.